The sniper and the wolf : a Sniper elite novel - McEwen, Scott; Koloniar, Thomas (Sniper elite novel, 2015)
"Hot on the trail of 'The Wolf,' a rogue Russian military sniper-turned-Chechen-terrorist, Gil Shannon turns from hunter to hunted when his mission is exposed by a traitor high up in US government. Shannon must turn to an unlikely ally--a deadly Russian special operative--to help even the odds. But when they discover that 'The Wolf' is just the tip of a global terrorist plot whose goal is to upend the US economy and the stability of the Western world, Shannon and his team of operatives must track the terrorists down before their plan comes to fruition"--